Personality does not Determine Internet Addiction: A Meta-Analysis - Astarini, Nadia; Yudiarso, Ananta (Makara Human Behavior Studies in Asia, 2020)
Internet addiction (IA) is the disruption of a person's life because of the excessive use of the Internet. Severe IA can contribute to relationship conflicts, poor well-being, and low productivity. Research has found that IA can be attributed to maladaptive thinking and specific personality traits and with the Big Five in particular. However, the results of previous studies have been somewhat inconsistent, with previous meta-analytical research showing insignificant correlations. This study was a replication of a previous meta-analytic study and sought to improve the accuracy and the reliability of previous findings using different and larger samples. A total of 11 studies with 16 correlations and 8,481 participants were examined for this study. It was found that the Big Five had insignificant correlations (r = −0.233–0.061) with medium to high heterogeneity (I2 = 70.7% to 96.8%) and no publication bias (E = 0.725), which was consistent with previous meta-analytical studies and implied that personality gave only a small contribution to IA behavior. Instrumental differences in the measurement of IA and personality (Big Five) and the participant sample characteristics were the main weaknesses in this meta-analysis.